Sources of economic growth in Zambia, 1970-2013: A growth accounting approach - Kelvin Mulungu; John N. Ng'ombe (Economies, 2017)
Most empirical work on sources of economic growth for different countries lack country-specific empirical evidence to guide policy choices in individual developing countries and previous studies of factor productivity tend to focus on the entire economy or a single sector. This provides fewer insights about a country's structural evolution. Unlike previous studies, our study builds on this by taking a more comprehensive approach in estimating Zambia's sources of economic growth by sectors-agriculture, industry, and service-in a systematic manner that yields insights into the country's sources of structural transformation. We use recently developed growth accounting tools to explicitly determine sources of economic growth at both national and sectoral levels in Zambia between 1970 and 2013. We use data from World Development Indicators and Zambia's Central Statistical Office. Results indicate that, on average, total factor productivity (TFP) contributes about 5.7% to economic growth. Sectoral analysis shows that agriculture contributes the least to GDP and that, within each sector, factors that contribute to growth differ. Structural transformation has been slow and contributed to the observed inefficiency. We outline the implications of the observed growth and provide recommendations.
Keywords: O40; O41; O55; 330; total factor productivity; growth accounting; economic growth; Zambia